2022
DOI: 10.3390/ma15165635
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Ornamental Stone Waste in the Manufacturing of Red Ceramics

Abstract: Brazil is one of the largest producers of ornamental stones in the world. The state of Espírito Santo has considerable social and economic relevance in the production of ornamental stones, particularly in exportation and the jobs that are directly related to this industry. The objectives of this work were to evaluate the effect of the incorporation of ornamental stone waste on the physical and mechanical properties of red ceramic manufactured using clays and waste from the state of Espírito Santo, and to colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Extractive waste recovery and recycling have been investigated in several studies (scientific papers, founded projects, etc.) [55][56][57][58]. Waste rocks, operating residues, and tailings, if managed separately, and depending on the specific characteristics of the ore deposits and/or the processing and working activities, can be considered as "mono-waste" landfill and properly exploitable for RM/CRM/SRM production.…”
Section: Raw Materials Critical Raw Materials and Secondary Raw Mater...mentioning
confidence: 99%
“…Extractive waste recovery and recycling have been investigated in several studies (scientific papers, founded projects, etc.) [55][56][57][58]. Waste rocks, operating residues, and tailings, if managed separately, and depending on the specific characteristics of the ore deposits and/or the processing and working activities, can be considered as "mono-waste" landfill and properly exploitable for RM/CRM/SRM production.…”
Section: Raw Materials Critical Raw Materials and Secondary Raw Mater...mentioning
confidence: 99%
“…The waste was mixed into the ceramic pastes at varying weights. Specimens were then manufactured through extrusion and fired at temperatures of 1050 • C and 1100 • C. The results showed improved properties in the ceramics with the inclusion of waste at both temperatures [11].…”
Section: Stone Waste As a Raw Materials For The Ceramic Industrymentioning
confidence: 99%
“…The granulometry of the granite waste benefited by multiwire gangsaw was also carried out. The results showed that the waste is a non-plastic material and that its fine particles contribute to better packaging and to the improvement of the final ceramic product [18].…”
Section: Granulometrymentioning
confidence: 99%
“…However, with the replacement of 40% and 50% it starts to decrease, but with superior resistance in ceramics fabricated only with clay. Another factor that must have significantly influenced this decrease was quartz, a mineral that composes the waste, which probably acted as an inert material and may have contributed to the formation of microcracks [18]. The flexural strength of ceramics is greatly influenced by the presence and shape of defects in their microstructures, such as grains and pores [28].…”
Section: Flexural Strengthmentioning
confidence: 99%
See 1 more Smart Citation